STUDENT AS A RESEARCHER IN HUMANITIES: CULTURAL LIMITATIONS FOR OBJECTIVITY - Kateryna Kuzan (Pavlo Tychyna Uman State Pedagogical University, 2017)
Cultural paradigm forms scientific objectivity. The goal of this article is to discuss the role of the culture in students` scientific practice. The present paper concentrates on analysis of the sociocultural factors that influence scientific inquiry. Within existing theoretical framework the author defines cultural competence which is necessary for student as a researcher. The conclusions are based on interviews of the students of Interdisciplinary Studies in Humanities. The study shows the students' understanding of the concept of «objectivity» and awareness of social and cultural influences on the research. Thelevel of development of students' cultural competence is also presented.